Métodos ágeis e aprendizagem organizacional em empresas orientadas a projetos - Rodrigues, Eliane Lima (2021)
The relevance of the use of agile methods in project environments is growing. Many organizations switched their project management method to agile project management seeking greater effectiveness in their deliveries and better responses to customers. Increasingly, the practice of agile project management is imposed in several organizations and this imposition generates a cultural resistance from the collaborators. The cultural resistance is a factor that can negatively influence organizational learning. Thus, the objective of this study is to understand how organizational learning occurs during the implementation of agile methods in the Project Management environment in project-oriented companies. The relevance of the study is to identify a coercive practice that enters the stable environment of the organization through the implementation of agile methods projects, causing resistance and negative effects on organizational learning. Therefore, we conducted a qualitative, exploratory-descriptive research, using a semi-structured interview tool for data collection, in addition to secondary data. The interviews were conducted with professionals in the field of project management. Twenty professionals who work or have already worked in Information Technology (IT) systems implementation projects were interviewed, belonging to two project-oriented companies, one small and one large. We used the MAXQDA software for analysis of the transcribed 20 interviews. The results allowed a list of factors, such as good practices in the implementation of agile projects and the influence of organizational learning in organizations. As a contribution, this research presents an overview of agile project implementation practices and organizational learning regarding customers, the project team, and organizational leaders. Finally, we expect this study may contribute to project-oriented companies as a support in the transfer of knowledge among individuals and teams and assertively multiplying learning.